Association of pulmonary leiomyoma with seborrheic keratosis - M Baghaei-vaji; S Shamsodini; A.R Habibi-Khorasani; H Tabrizchi (Journal of Kerman University of Medical Sciences, 1997)
A 58 year old man was referred to suegery clinic due to dyspnea and left sided chest wall pain for three months duration.during the last 18 months some monomorph disseminated hyperkeratotic skin lesions appeared on his face and trunk.after worlup and evaluation of the patient,he underwent thoracotomy with indication of presence of a mass in the left lung.the operative finding was a huge solid round tumor arising from left lower lobe which was located inside the lung parenchyma and had loose attachment to pericardium.the tumor was removed by left lower lobectomy.pathological report of tumor in the lung.association of abrupt seborrheic keratosis and underlying malignancies indicates the sign of leser-trelat.up to 1993,a total forty eight cases of this syndrome has been reported,of which one case was diagnosed as leiomyoblastoma.since reports of definitive diagnosis of this syndrome is rare,and due to metastasis which is reported in leiomyma,though it is very rare,we can conclude that the presented patient can be a case of leser trelat syndrome or a very rare association of the two different diseases.